2019
DOI: 10.1111/jppi.12318
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Risk of Sexual Abuse for Adults With Intellectual and Developmental Disabilities from an Ecological Framework

Abstract: Current research on sexual violence perpetrated against individuals with intellectual and developmental disabilities (IDD) focuses on rates of victimization and individual risk factors. This research suggests that individuals with IDD are at a greater risk for sexual violence compared with the general public. At this time, there is no comprehensive theoretical framework to explain sexual abuse risk factors for individuals with IDD. This article describes such a framework by examining how an ecological perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…It is important to understand both the contextual risks and the impairment-related risks so that as a society we can work towards taking action against this scourge without simply blaming it on the attributes of the individuals with intellectual disabilities. In line with this, Curtiss and Kammes (2020) argued that individual factors on their own do not cause sexual violence; hence, the interplay between the impairment and the environment should be considered. Phasha and Myaka (2014), in their study on factors contributing to the vulnerability of teenagers with intellectual disabilities to sexual abuse found an interaction of individual, family and community factors as central in putting the teenagers at risk.…”
Section: Literature Reviewmentioning
confidence: 93%
See 2 more Smart Citations
“…It is important to understand both the contextual risks and the impairment-related risks so that as a society we can work towards taking action against this scourge without simply blaming it on the attributes of the individuals with intellectual disabilities. In line with this, Curtiss and Kammes (2020) argued that individual factors on their own do not cause sexual violence; hence, the interplay between the impairment and the environment should be considered. Phasha and Myaka (2014), in their study on factors contributing to the vulnerability of teenagers with intellectual disabilities to sexual abuse found an interaction of individual, family and community factors as central in putting the teenagers at risk.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Although the trends may vary by context, sexual violence against people with intellectual disabilities is an issue of concern in both high income and low to middle income countries among children and adults with this type of disability (Curtiss & Kammes 2020;Lin et al 2009;Smeaton & Franklin 2018). In Taiwan, Lin et al (2009) reported that sexual assault among people with intellectual disabilities comprised more than 50% of the statistics of sexual assault across all types of disabilities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The social-ecological framework of bullying proposes that "a bullying interaction occurs not only because of individual characteristics of the child who is bullying, but also because of actions of peers, actions of teachers and other adult caretakers at school, physical characteristics of the school grounds, family factors, cultural characteristics, and even community factors" (Swearer & Doll, 2001, p. 10). Disability scholars have recognized the importance of research frameworks that consider factors beyond the individual-level (e.g., impairment type) as factors at the micro (e.g., school climate) and macrosystems (e.g., child protection policies and disability rights movement) have a profound effect on disability-based violence (Curtiss & Kammes, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Extensive research has investigated the use of violence, especially domestic, physical, and sexual violence, toward people with different disabilities, by relatives, spouses, neighbors, and caregivers (McGowan & Elliott, 2019; Stern et al, 2020). Studies have found that people with disabilities experience violence more frequently compared with the general population, and women with disabilities are exposed to violence more often than their male counterparts (Curtiss & Kammes, 2020; Valentine et al, 2019; van der Heijden et al, 2019).…”
Section: Introductionmentioning
confidence: 99%